Prevalence of migraine and its associated factors among undergraduate students at the Jaffna premises of University of Jaffna, Sri Lanka - Rathnayaka, A.L.U.; Weerasingha DH1, D.H.; Jegapragsh, V.; Jeevagan, V (University of Jaffna, 2024)
Introduction: Migraine is a neurological condition categorized as a primary headache disorder by the International Classification of Headache Disorders (ICHD-3). Migraine affects about 30% of the global population; particularly, students seem to be more susceptible, with rates of 20% to 52%. Academic stress, irregular lifestyles, and genetics increase the risk for migraine and found to negatively impact academic performance and quality of life. Objective: To determine the prevalence of migraine and its associated factors among undergraduate students at the Jaffna premises of University of Jaffna, Sri Lanka. Methodology: A descriptive cross-sectional study was conducted among undergraduates at University of Jaffna. A total of 464 students were recruited from selected faculties using a proportionate random sampling method. To gather data, a self-administered questionnaire was used. The data was analyzed using SPSS 27. A chi-square test was performed to identify the associated factors. Ethical approval for the study was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Results: This study investigated migraine prevalence in 464 participants including the age range from 20 to 28 years (mean age: 23.94, SD=1.839). Female: Male ratio is 1:1. Overall, the prevalence of migraine is 7.5%. Prevalence was highest in ages 26-28 (11.88%), females (11.44%) and undergraduates following medical-related courses (25.74%). Obesity (9.41%) and overweight (8.22%) exhibited higher prevalence variations. Also, those with a family history of migraine, inadequate sleep, and lack of exercise had a high prevalence. The identified factors associated with migraines include gender (p=0.001), marital status (p<0.001), course of study (p<0.001), family history of migraines (p<0.001), duration of sleep (p<0.001), tea/coffee consumption (p=0.045), and exposure to strong odours (p=<0.001). Conclusion: The overall migraine prevalence was 7.5% including higher rates among females, married individuals, and those with a family history of migraines. Lifestyle factors, including inadequate sleep and exposure to strong odors, also play a role. This study highlights the role of demographic factors and lifestyle choices in understanding migraine prevalence by informing targeted preventive measures.
Keywords: Migraine; Undergraduates; Prevalence; Headache; Factors